Insights into the naturally acquired immune response to Plasmodium vivax malaria. Issue 2 (7th January 2016) - LONGLEY, RHEA J.; SATTABONGKOT, JETSUMON; MUELLER, IVO
SUMMARY: Plasmodium vivax is the most geographically widespread of the malaria parasites causing human disease, yet it is comparatively understudied compared with Plasmodium falciparum. In this article we review what is known about naturally acquired immunity to P. vivax, and importantly, how this differs to that acquired against P. falciparum. Immunity to clinical P. vivax infection is acquired more quickly than to P. falciparum, and evidence suggests humans in endemic areas also have a greater capacity to mount a successful immunological memory response to this pathogen. Both of these factors give promise to the idea of a successful P. vivax vaccine. We review what is known about both the cellular and humoral immune response, including the role of cytokines, antibodies, immunoregulation, immune memory and immune dysfunction. Furthermore, we discuss where the future lies in terms of advancing our understanding of naturally acquired immunity to P. vivax, through the use of well-designed longitudinal epidemiological studies and modern tools available to immunologists.